Effect of ethanolic extract of Rosa centifolia against doxorubicin induced nephrotoxicity in albino rats - S.K. Nimbal (Elsevier, 2021)
Background: Efficacy of Anthracycline derivative Doxorubicin (Dox) has been proven in several malignancies such as breast cancer, Hodgkin and non-Hodgkin lymphoma, acute leukemia, lung, thyroid and ovarian cancer. However its clinical usefulness is restricted due to its cardiotoxicity and nephrotoxicity. Rosa centifolia belongs to family Rosaceae and in Ayurveda it is claimed for use in renal disorders. The main phyto-constituents of the plant are terpenoids, glycosides, flavonoids, tannins, phenolic compounds, pro-antroocyanides, pectin and riboflavin. Objective: To investigate the ameliorative role of ethanolic extract of petals of R. centifolia in doxorubicin induced nephrotoxicity in rats. Materials and methods: Nephrotoxicity was produced by administration of doxorubicin (2.5 mg/kg b.w., i.p. alternate day) in six equal injections for two weeks to achieve a cumulative concentration of 15 mg/kg. Low (LERC - 100 mg/kg p.o.) and high (HERC - 200 mg/kg p.o.) dosees of ethanolic extract of petals of R. centifolia was administered as a pretreatment prior to doxorubicin administration. The general parameters such as body weight, food and water intake were measured throughout the study period. Serum biomarkers such as blood urea nitrogen (BUN), serum creatinine and albumin were measured before treatment and at the end of the experiments. Anti-oxidant enzymes such as glutathione (GSH), melonldehyde (MDA), catalase (CAT) and superoxide dismutase (SOD) were monitored after the last dose. Nephrotoxicity was assessed through histopathological analysis. Results: The repeated administration of doxorubicin produces several morphological changes including reduction in the body weight as well as decreased food and water consumption. Serum biomarkers such as BUN, serum creatinine were increased and albumin concentration was decreased. The GSH, SOD and CAT concentrations were decreased, whereas MDA concentration was increased. Deteriorating changes in the histological architecture of kidney tissue were observed. In the LERC and HERC pretreated groups following changes were observed in dose dependent manner: increase in body weight, food and water intake (p < 0.05 and p < 0.01), decrease in the BUN (p < 0.05 and p < 0.01) and serum creatinine (p < 0.05 and p < 0.05) concentrations respectively. The significant increase in the albumin (p < 0.01) concentration was observed only in HERC. The pretreatment with LERC and HERC increased the antioxidant enzymes concentrations i.e. GSH (p < 0.01 and p < 0.01), SOD (p < 0.01 and p < 0.01), CAT (p < 0.05 and p < 0.01) and decreased the MDA concentration (p < 0.05 and p < 0.01) respectively. Histopathological studies showed that the pretreatment with low and high doses of ethanolic extract of petals of Rosa centifolia LERC and HERC groups minimized the tubular damage and reduced the inflammation as compared to doxorubicin treated group. Conclusion: The biochemical and histopathological data from the present study clearly support the nephroprotective effect of ethanolic extract of petals of R. centifolia, which might be credited to its anti-oxidant property.